Intramolecular anti-phosphinoauration of alkynes: an FLP-motivated approach to stable aurated phosphindolium complexes - Arndt, Sebastian; Hansmann, Max M.; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Chemistry - a European journal, 2017)
The synthesis of aurated phosphindolium complexes from easy accessible 1,5-alkynylphosphine derivatives has been studied by using gold(I) complexes featuring carbene and phosphine ligands as initiators. Upon formation of the mixed phosphine NHC/phosphine gold species, elevated temperatures induced the cyclization to give stable aurated phosphindolium salts, which is supported by DFT calculations. The key elementary step that comprises a yet unknown anti-phosphinoauration of an unactivated alkyne is favored if bulky NHC ligands are used which was analyzed by kinetic measurements. This concept could furthermore be extended to neutral (phosphindolium)AuCl complexes featuring the yet unknown phosphindole ligand.
Gesehen am 22.08.2017